Textual Bond ‘krome togo’ [moreover]: Contextual Modifications - N. V. Koneva; E. A. Starodumova (Научный диалог, 2021)
The service unit moreover is considered from the point of view of functioning in the text. The relevance of the study is due, on the one hand, to the inclusion of the research in the study of the linguistics of the text and linguistic units that serve as means of communication in the text, on the other hand, to the lack of special descriptions of text clips in research and lexicographic sources. The novelty of the research is seen in the fact that an attempt was made to describe the general regularities of the functioning of the bond moreover in the text, characteristic contexts were identified. The description of this word in scientific literature and lexicography is analyzed. In the course of the analysis, it was revealed that the unit also functions as a text bond with the value of attachment. A total of 5 contextual modifications have been established. Three modifications are related to the degree of significance of the information in the attached comment. Two more modifications relate to the text-forming function, which is performed by the bond moreover. To identify the features of the functioning of the studied bond, examples of its use in various journalistic and literary texts were analyzed.